Erythrocyte Magnesium Levels in type I and type II Iraq diabetic patients effect of antidiabetic treatment - Kazaa, Faris Abdul Kareeml; Abdulaziz, Lewai S.; Naji, Ragad I. (AL-Kindy College Medical Journal, 2012)
Background: Direct measurement of intracellular magnesium using erythrocytes has been suggested as a sensitive indicator for the estimation of body magnesium store. Marked depletion in plasma and erythrocyte magnesium levels was particularly evident in diabetic patients with advanced retinopathy and poor diabetic control. While insulin has been shown to stimulate erythrocyte magnesium uptake, hyperglycemia per se suppressed intracellular magnesium in normal human red cells. Aim of the study: To investigate the erythrocyte magnesium level in Iraqi type I and II diabetic patients, with specific emphasis on the effect of both, metabolic control and the type of antidiabetic treatments. Methods: Sixty two diabetic patients (7 with type I and 55 with type II diabetes mellitus) recruited from the outpatient diabetes clinic at the Specialized Center For Endocrine Diseases-Baghdad, during the period from 1st October 2005 to 28th February 2006. Eighteen non-diabetic normomagnesemic healthy controls matched for age and sex were participated in this study. Of the diabetics, 22 were using insulin (7 with type I and 15 with type II diabetes mellitus), 40 were taking oral antidiabetic agents (All with type II diabetes mellitus) and none were using both. Serum and erythrocyte magnesium concentration were measured for both groups, and Glycated hemoglobin levels were estimated only for diabetics. Results : Mean serum and erythrocyte magnesium levels were significantly (p<0.001) lower in the diabetic group as compared to controls. Serum level of magnesium was not a significant predictor of erythrocyte magnesium concentration. No significant correlation was observed between HbA1c and erythrocyte magnesium. Significantly (p<0.001) lower serum magnesium levels were consistently evident through the entire diabetic subgroups as compared to controls. Erythrocyte magnesium contents were significantly (p<0.001) reduced in patients with type I , type II and type II receiving oral antidiabetic agents, but not in patients with type II receiving insulin (p= 0.120 ), as compared to controls. Significant difference in erythrocyte magnesium levels was observed between patients with type II receiving oral antidiabetic agents and those receiving insulin (p<0.001). The frequency of magnesium deficiency in diabetic patients, as judged by a lower serum magnesium reference limit was constantly 100% in all subgroups. While, judgments based upon a lower erythrocyte magnesium reference limit, discloses variable frequencies in diabetic subgroups. conclusion: The near normal erythrocyte magnesium levels in type II insulin-receiving patients, could be credited to the stimulatory action of exogenous insulin on cellular magnesium uptake and may indicate a possible role of insulin treatment as a potential implications on health policy, by ameliorating cellular magnesium depletion in the continuously expanding diabetic population.